Early signs of geodynamic activity before the 2011–2012 El Hierro eruption. (February 2017) - López, Carmen; García-Cañada, Laura; Martí, Joan; Domínguez Cerdeña, Itahiza
Graphical abstract: Highlights: Precursory tectonic activity preceding the El Hierro eruption is analyzed. Very early signs of regional anomalous activity are identified starting in 2003. Intensity of anomalous activity increased in 2007 and accelerated three months before the eruption. Link between regional geodynamics and volcanic activity in the Canary Islands. Abstract: The potential relation between mantle plume dynamics, regional tectonics and eruptive activity in the Canary Islands has not been studied yet through the analysis of long-time series of geophysical observational data. The existence of highly reliable seismic and geodetic data has enabled us to study from 1996 to 2014 the geodynamic evolution of the North Atlantic Azores-Gibraltar region (including the NW African margin) and its relationship with recent volcanic activity in El Hierro (Canary Islands). We compiled a new and unified regional seismic catalog and used long time-series of digital 3D surface displacements recorded by permanent GPS stations in the region. A joint regional- and local-scale analysis based on these data enabled us to identify signs of anomalous tectonic activity from 2003 onwards, whose intensity increased in 2007 and finally accelerated three months before the onset of the volcanic eruption on El Hierro in October 2011. Activity included the occurrence of regional extension and an uplift process affecting the southern Iberian Peninsula, NW Africa, and the Canary Islands. We interpret these observations as early signs of the geodynamic activity, which led to El Hierro eruption and the subsequent episodes of magma intrusion. Results point to the significant contribution of the mantle plume dynamics (i.e. external forces) in this renewed volcanic activity in the Canary Islands and emphasize the role of mantle dynamics in controlling regional tectonics.